2009
DOI: 10.1007/s10533-009-9311-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation varies spatially and seasonally in linked stream-lake ecosystems

Abstract: We performed surveys of nitrogen (N 2 )-fixation in three oligotrophic lake-stream systems in the Sawtooth Mountains of central Idaho to address two questions: (1) Which habitat types within linked lake-stream systems (lake pelagic, lake benthic, and stream) exhibit the highest rates of N 2 fixation?, and (2) How does N 2 fixation compare to the hydrologic flux of nitrogen? A seasonal survey showed that N 2 fixation in a single lake and its outlet stream peaked in late summer, when hydrologic N fluxes were low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 52 publications
4
23
0
Order By: Relevance
“…Some studies have indicated that N-fixing cyanobacteria become dominant in summer with a nitrogen shortage (Mugidde et al 2003;Marcarelli and Wurtsbaugh 2009;Paterson et al 2011). However, N-fixing cyanobacteria did not dominate the phytoplankton community in several additional studies under analogous circumstances (Havens et al 2003;Scott and McCarthy 2010;Gikuma-Njuru et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that N-fixing cyanobacteria become dominant in summer with a nitrogen shortage (Mugidde et al 2003;Marcarelli and Wurtsbaugh 2009;Paterson et al 2011). However, N-fixing cyanobacteria did not dominate the phytoplankton community in several additional studies under analogous circumstances (Havens et al 2003;Scott and McCarthy 2010;Gikuma-Njuru et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…N fixation, like all biogeochemical processes, is a spatially and temporally patchy process; thus small-scale experiments may misrepresent its extent. There is also growing appreciation for the potential N fixation in benthic habitats (Marcarelli and Wurtsbaugh 2009) that is difficult if not impossible to quantify in microcosms. Thus, an approach to measuring N fixation that integrates over space and time has become increasingly needed to understand how eutrophication changes the importance of N fixation in aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, and perhaps more plausibly, if the majority of DON results from within-lake biological uptake of nitrate, as nitrate concentrations decline with increasing lake landscape position less new autochthonous organic nitrogen would be produced. With little landscape variability in rates of nitrogen fixation or uptake in streams (Arp and Baker 2007;Marcarelli and Wurtsbaugh 2009), DON concentrations would cease to increase with increasing lake landscape position as nitrogen was primarily cycled between inorganic and organic fractions in association with biological processes.…”
Section: Landscape Controls On Dissolved Nitrogenmentioning
confidence: 99%